PERSEPSI GURU TERHADAP GAYA KEPEMIMPINAN KEPALA SD NEGERI 11 KAPEH PANJI KECAMATAN BANUHAMPU AGAM - Fakhri Syafrizal (IAIN Batusangkar, 2016)
This qualitative case study was aimed at disclosing the teachers’ perception on headmaster’s leadership style of Primary School 11 Kapeh Panji. The interview and observation were used as instruments to collect the data. The results revealed that the headmaster of Primary School 11 Kapeh Panji was democratic, humorous and communicative. The headmaster was also as motivator in this school. Keywords: Teachers’ Perception, Leadership Style, Headmaster, Primary School 11 Kapeh Panji